Validitas E-LKPD Berbasis Strategi KWL (Know-Want-Learned) Pada Materi Ekosistem Untuk Melatih Keterampilan Metakognitif : (Validity of E-LKPD Based on KWL (Know-Want-Learned) Strategy on Ecosystem Material to Train Metacognitive Skills) - Sadikin, Agriani; Dama, Lilan; Husain , Ilyas H.; Mardin, Herinda; Katili, Abubakar Sidik (BIODIK, 2025)
Biology learning tends to be teacher-centered, resulting in a lack of active student involvement and limited metacognitive skill development. This study aims to determine the validity of the E-LKPD based on the KWL (Know-Want-Learned) strategy on ecosystem material to train students' metacognitive skills. The study used the R&D method with the ADDIE model limited to the Development stage. The research subjects were 18 grade X students of SMA Negeri 6 Gorontalo. Data were collected through teacher interviews and validation by two validators (media and material). The validation results showed that the E-LKPD based on the KWL strategy obtained a "very valid" category with an average percentage of 99% from media experts and 98% from material experts. The developed E-LKPD is suitable for use in biology learning to train students' metacognitive skills and is ready for the implementation stage. Pembelajaran biologi yang cenderung masih berpusat pada guru menyebabkan kurangnya keterlibatan aktif peserta didik dan terbatasnya pengembangan keterampilan metakognitif. Penelitian ini bertujuan untuk mengetahui validitas E-LKPD berbasis strategi KWL (Know-Want-Learned) pada materi ekosistem untuk melatih keterampilan metakognitif peserta didik. Penelitian menggunakan metode R&D dengan model ADDIE yang dibatasi hingga tahap Development. Subjek penelitian adalah peserta didik kelas X SMA Negeri 6 Gorontalo yang berjumlah 18 orang. Data dikumpulkan melalui wawancara guru dan validasi oleh dua validator (media dan materi). Hasil validasi menunjukkan E-LKPD berbasis strategi KWL memperoleh kategori "sangat valid" dengan rata-rata persentase 99% dari ahli media dan 98% dari ahli materi. E-LKPD yang dikembangkan layak digunakan dalam pembelajaran biologi untuk melatih keterampilan metakognitif peserta didik dan siap untuk tahap implementasi.